2020
DOI: 10.3892/etm.2020.8413
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin protects myocardial cells in mice with acute myocardial infarction through inhibiting RhoA/ROCK pathway

Abstract: Protective effect of fluvastatin (Flu) on myocardial cells in mice with acute myocardial infarction (AMI) and the mechanism were explored. Forty C57B/L6 mice in similar physiological status were selected and randomly divided into sham operation (Sham) group (n=10), AMI group (n=10), Flu group (n=10) and Flu + Angiotensin II (Ang II) (Ang II) group (n=10). The pathological changes in heart tissues were detected via hematoxylin and eosin (H&E) staining, and apoptosis of myocardial cells was detected via terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that the oxidative stress levels are significantly elevated in AMI, which could cause myocardial cell dysfunction and damage [ 47 , 48 ]. In addition, excessive oxidative stress and an inflammatory response could promote the occurrence of heart failure in patients with AMI [ 49 ]. Based on the above evidence, we speculated that S100A12 may promote the inflammatory response, oxidative stress, and myocardial damage after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the oxidative stress levels are significantly elevated in AMI, which could cause myocardial cell dysfunction and damage [ 47 , 48 ]. In addition, excessive oxidative stress and an inflammatory response could promote the occurrence of heart failure in patients with AMI [ 49 ]. Based on the above evidence, we speculated that S100A12 may promote the inflammatory response, oxidative stress, and myocardial damage after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the sections were added to 50 μL of DAB substrate solution and left to incubate for 10 minutes at room temperature. At last, the sections were sealed with glycerol, and a light microscope was employed for counting and photographing [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Xu et al have suggested that leonurine inhibited myocardial apo ptosis and improved myocardial function in rat model by activating the PI3K/AKT/GSK3β pathway [ 33 ]. Yi et al has found that inhibition of RhoA/ROCK pathway significantly mitigated AMI-induced myocardial apoptosis in mice [ 34 ].The analogical results were obtained in our study. We found that AMI modeling inhibited the AMPK/mTOR pathway and induced myocardial apoptosis.…”
Section: Discussionmentioning
confidence: 99%